CLINICAL MANIFESTATIONS OF POLYCYSTIC OVARY SYNDROME - Sparic, Radmila M; Zlatar, Jelena; Nikolić, Luka; Opalić Palibrk, Milica; Radić, Lena; Bjekić Macut, Jelica; Ognjanović, Sanja; Macut, Djuro (Medical Research, 2024)
Polycystic ovary syndrome, commonly abbreviated as PCOS, as the most common endocrine disorder the in women of reproductive age, is a multifaceted disease characterized by various hormonal imbalances and a great degree of variation in its clinical presentation. This, coupled with its etiology and pathogenesis being incompletely understood, results in a broad disease spectrum that is challenging to accurately diagnose and manage. The primary clinical features which PCOS commonly manifests with include hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology, though all three are not necessarily present in all PCOS patients. Hyperandrogenism, manifesting as hirsutism, acne, and male-pattern alopecia, significantly affects both the physical and psychological wellbeing of these patients. Ovulatory dysfunction, presenting as irregular menstrual cycles due to oligo/anovulation, is an important element of PCOS’s clinical presentation and leads to the infertility that some of these patients’ experience. PCOS is commonly associated with insulin resistance and consequent hyperinsulinemia and metabolic disorders, seen in these patients. Subsequently, women affected with PCOS are at greater risk of obesity, dyslipidemia, diabetes, and cardiovascular diseases, particularly later in life. The rate of mood disorders, namely depression and anxiety, is also increased in this population. The complex nature of this syndrome makes difficulties in patient care, and its chronic nature emphasizes a proactive stance when it comes to treatment, but also a careful assesment of all the elements of the disease.